Analysis of the capacity changes in the "Garajevac-istok" excavation by applying the GIS technology - Borisov, Mirko A.; Simić, Radovan V.; Petrović, Vladimir M.; Bojović, Bogdan B. (Vojnotehnički glasnik / Military Technical Courier, 2018)
The paper discusses the concept of construction and monitoring of capacity changes - the volume of the "Garajevac-Istok" excavation (mine), located in the cadastral municipality of Novi Bečej. Namely, in the earlier period, the physical surface of the Earth and geospace in general were shown two-dimensionally (2D), in a plane, by some of the cartographic methods (contour lines, points heights, hypsometry) or three-dimensionally (3D), by modeling of reliefs and relief cards. The cartographic principles of terrain making and visualizing on relief mapping models allow the creation of 3D views, but not enough quality and engineering precise 3D terrain models. In addition, there is a possibility of quantitative and qualitative assessment of the terrain on the mentioned models not to be accurate enough. With new technologies, the 3D geospatial display mode changes, and the concept of digital terrain modeling (DTM) is being applied. The main goal of the work is to create 3D models and to give an analysis of the "Garajevac-Istok" mine for a certain period of exploitation.